On certain aspects of estimation of areal rainfall - MEHRA, HC (MAUSAM, 1986)
Network design .has of late assumed very great importance in .all water resources investigations. Though many techniques are available for planning network for different hydrological parameters yet many difficulties are experienced in the collection of observations with desired accuracy. Spatial variation of the hydrological variable is an important factor, which has to be duly considered. In addition to this, there are various practical difficulties in collecting the observations as dictated by theoretical considerations The mountaineous catchments further add to these problems. In the present paper, an attempt bas been made to study the precipitation network design using Kagan's technique (1966). It also highlights the various practical field problems involved in implementing the desired network from theoretical considerations. A case study has been done for 'Purna catchment', a tributary of river Tapi in Maharashtra.